P169 Analysis of left ventricle dysfunction, pulmonary disease and nailfold videocapillaroscopy patterns in asymptomatic patients with early systemic sclerosis. (20th April 2020) - Masini, Francesco; Monaco, Lucio; Gjeloshi, Klodian; Pinotti, Emanuele; Ferrara, Roberta; Salvatore, Teresa; Cuomo, Giovanna
Abstract: Background: Systemic sclerosis (SSc) is a multi-system connective tissue disease characterized by microvascular damage, inflammation and fibrosis. The aim of our study is to investigate a possible correlation between nailfold videocapillaroscopy patterns and internal organ involvement in patients with early SSc. Methods: We enrolled 40 patients with early SSc according to LeRoy criteria and performed echocardiogram, pulmonary function tests (PFTs) and nailfold videocapillaroscopy. Results: 20 patients had early pattern and 20 active pattern. A comparative analysis between SSc patients and healthy controls showed an alteration of mitral annular plane systolic excursion (MAPSE) (1.5±0.1 vs 1.7±0.1; p < 0.001), respectively; an increased occurrence of diastolic dysfunction (11/40 vs 0/21; p = 0.01) respectively; a higher values of systolic pulmonary arterial pression (PAPs) (32±6 vs 22±6; p < 0.001) and a higher frequency of patients with pulmonary hypertension (12/40 vs 0/21; p = 0.005) in SSc group. The patients with an active capillaroscopic pattern showed a trend of reduction in MAPSE, diastolic dysfunction, contractility of the right ventricle and pulmonary function tests parameters. We observed a correlation between myocardial and pulmonary vascular damage and between myocardial and pulmonary fibrosis, with lower DLCO value in patients with diastolic dysfunction (64±17 vs 85±9; p < 0.0001). Conclusion: A subclinical myocardial damage in these patients may be observed also in the absence of symptoms. In fact, in our study it can be noted that asymptomatic patients present a reduction in the linear myocardial contractility. Furthermore, we observed the presence of grade I diastolic dysfunction in 27.5% of cases, a sign of an initial stiffening of the wall, likely due to a fibrotic damage. In our study linear contractility emerges to be not correlated with the presence of diastolic dysfunction. Such data is very intriguing if we consider that in many studies the resolution of linear contractility with conserved ejection fraction correlated with subendocardial damage induced by microcirculation alterations. The hypothesis is the presence of a double framework at the myocardial level: a vascular damage and the presence of increased inflammation and fibrosis. The presence fibrosis is correlated between the various organs, with the values of DLCO strongly correlating with the presence of diastolic dysfunction; instead DLCO values do not correlate with pulmonary pressure values. The analysis of the capillaroscopic parameters we observed how in the early pattern the presence of vascular damage with MAPSE and PAPs alterations and presence of pulmonary hypertension emerge, while passing from early to active the presence of fibrotic damage becomes evident, the diastolic dysfunction passing from 15% to 40% and DLCO passing from 83% to 75%. The presence of subclinical cardiac and pulmonary damage in patients with systemic sclerosis and that this damage is closely related to the capillaroscopic pattern. Disclosures: F. Masini: None. L. Monaco: None. K. Gjeloshi: None. E. Pinotti: None. R. Ferrara: None. T. Salvatore: None. G. Cuomo: None.